Struktur Kemampuan Siswa dalam Menyelesaikan Masalah Matematika Berdasarkan Taksonomi SOLO - Widayanti, Lilis (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
This study aims to implement the Structure of Observed Learning Outcomes (SOLO) Taxonomy to describe the structure of students' mathematical problem-solving abilities and to explain their thinking processes regarding the problem of the System of Linear Equations with Two Variables ( SLETV). A framework to examine the structure of students' mathematical problem solving skills is essential, because their understanding of basic mathematical ideas is useful in everyday life. This research methodology uses descriptive qualitative applied to eighth grade students at SMPN 5 Malang. To determine the structure of students' skills, we collected information through interviews and responses from problem solving tests. The findings revealed that students' competencies were broken down into unistructural, multistructural, and relational levels, without students reaching a complex prestructural or abstract level. This study innovatively presents visualizations of students' problem-solving frameworks, grounded in Chick's (1998) theory. The results of the study indicate that most students are at the multistructural level, namely, they can recognize relevant information but have not achieved the ability to integrate concepts comprehensively. This study provides guidance for educators to analyze students' abilities in solving mathematical problems using an effective evaluation tool, namely using the SOLO taxonomy. Penelitian ini bertujuan untuk mengimplementasikan Taksonomi Structure of Observed Learning Outcomes (SOLO) untuk mendeskripsikan struktur kemampuan pemecahan masalah matematika siswa dan menjelaskan proses berpikir mereka terkait masalah Sistem Persamaan Linear Dua Variabel (SLETV). Kerangka kerja untuk mengkaji struktur keterampilan pemecahan masalah matematika siswa sangat penting, karena pemahaman mereka terhadap ide-ide matematika dasar berguna dalam kehidupan sehari-hari. Metodologi penelitian ini menggunakan deskriptif kualitatif yang diterapkan pada siswa kelas delapan di SMPN 5 Malang. Untuk mengetahui struktur keterampilan siswa, kami mengumpulkan informasi melalui wawancara dan tanggapan dari tes pemecahan masalah. Temuan penelitian mengungkapkan bahwa kompetensi siswa dipecah menjadi tingkat unistruktural, multistruktural, dan relasional, tanpa siswa mencapai tingkat prastruktural atau abstrak yang kompleks. Penelitian ini secara inovatif menyajikan visualisasi kerangka kerja pemecahan masalah siswa, yang didasarkan pada teori Chick (1998). Hasil penelitian menunjukkan bahwa sebagian besar siswa berada pada tingkat multistruktural, yaitu mereka dapat mengenali informasi yang relevan tetapi belum mencapai kemampuan untuk mengintegrasikan konsep secara komprehensif. Penelitian ini memberikan panduan bagi para pendidik untuk menganalisis kemampuan siswa dalam memecahkan masalah matematika menggunakan alat evaluasi yang efektif, yaitu menggunakan taksonomi SOLO.